UMP-KPT 1Malaysia Rafting X-Ploration Sees Encouraging IPT Participation - UMP, PNC
The UMP-KPT 1Malaysia Rafting X-ploration in Pahang saw encouraging participation from the local institutions of higher learning (IPT) with thirty-five teams, comprising 455 members, arriving at the last leg of the expedition in Pekan Riverfront.